Building the blocks of protocol design and analysis challenges and lessons learned from case studies on mobile ad hoc routing and micro-mobility protocols. - Bai, Fan (Computer communication review.)
With the emergence of new application-specific sensor and Ad-hoc networks, increasingly complex and custom protocols will be designed and deployed. We propose a framework to systematically design and evaluate networking protocols based on a 'building block' approach. In this approach, each protocol is broken down into a set of parameterized modules called "building blocks", each having its own specific functionality. The properties of these building blocks and their interaction define the overall behavior of the protocol. In this paper, we aim to identify the major research challenges and questions in the building block approach. By addressing some of those questions, we point out potential directions to analyze and understand the behavior of networking protocols systematically. We discuss two case studies on utilizing the building block approach for analyzing Ad-hoc routing protocols and IP mobility protocols in a systematic manner.